THE CONTRIBUTION OF NON-FISHING LIVELIHOOD ACTIVITIES FISHERMAN HOUSEHOLD ECONOMY IN DOMPAS VILLAGE BUKIT BATU DISTRICT BENGKALIS REGENCY - Enrini, Maharatih; Yulinda, Eni; Amrifo, Viktor (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This study was conducted in November 2016 in Dompas Village Bukit Batu District Bengkalis Regency. The purpose of this study was to describe the activity of a living outside the business of fishing is carried out by fishermen household members, analyze the contribution of business activity of a living outside the fishery for fishermen household economy. The method used in this study is a survey method. The population in this study are members of households of fishermen in the village Dompas which has activities outside the sideline income to fishing with a total population of 30 Household.Activities living out of fishing is done fishermen household consists of trade activity, gardening, building work, watch store, and the labor market. Activities husband living outside of fisheries such as gardening, building work, and the labor market and in doing at the time did not undertake fishing. wife living activities outside of fisheries such as gardening and trade and activities of children living outside of fisheries such as trade and watch store. The contribution of the activity of a living outside the fishery business made a great contribution to the household economy Dompas fishing village. Contributions activity husbands living outside the fishery business, amounting to 40.82%, 27.29% of wives and children of 31, 89%. Contribution income households living fishing activities outside the fishery business amounted to 44.04%, while the contribution of the fishery business amounted to 55.96%.Keywords: Contribution, Livelihood activities, Economy household